Intravascular visualization methods in estimating vasculopathy of a transplanted heart - S. A. Sakhovsky; N. N. Koloskova; A. Yu. Goncharova; B. L. Mironkov (Вестник трансплантологии и искусственных органов, 2019)
One of the pathognomonic signs of сardiac allograft vasculopathy is concentric intimal hyperplasia, which can be assessed by intravascular imaging techniques. Early detection of cardiac graft vasculopathy and timely correction of immunosuppressive therapy can help slow the pathological process and, as a result, increase the functional survival of the heart graft. Recently, the method of intravascular optical coherence tomography, which improves the accuracy of the assessment of the layers of the vascular wall and is considered as an alternative to intravascular ultrasound, is becoming more and more common. This review focuses on the importance of modern methods of intravascular imaging in the early diagnosis of cardiac graft vasculopathy and the identification of predictors of this disease.